Terminologi Evaluasi Pendidikan Dalam Surat Al-‘Ankabu>t Ayat 2-3 dan Al-Zalzalah Ayat 7-8 (Studi Komparasi Tafsir Al-Qura>n Al-‘Az}im Karya Ibnu Kası>r dan Tafsir Al-Azha>r Karya Buya Hamka) - Inggriani Putri, Rachma Meilia; Salim, Hakimuddin; Azani, Mohammad Zakki (MODELING: Jurnal Program Studi PGMI, 2023)
Evaluation is a very important part of measuring the success of the learning process. The purpose of holding a learning assessment is to understand the extent to which students have experienced development or progress in three dimensions, namely cognitive, affective and psychomotor. The evaluation carried out by teachers when viewed from the fact that the world of education carried out by teachers that often occurs is not true. For example, when educators give exam questions to their students, but the questions given are not all in accordance with the material that educators have delivered to their students in the classroom during learning. This can result in low student learning outcomes. This study aims to provide an analysis of the principles of evaluation and types of evaluation in Sura Al-'Ankabut verses 2-3 and Sura Al-Zalzalah verses 7-8, as well as their relevance in education today. To obtain valid data, researchers use a qualitative paradigm with a muqaran interpretation approach, data collection techniques using documentation (document studies) with descriptive-analytical data analysis. The principles of evaluation in these two letters can be concluded including 1) The Hadaf Principle 2) the Al-kamal principle 3) the istimrar principle 4) the maudhuiyyah principle 5) the alfariq principle, and 6) the 'adula principle. The type of evaluation contained in these two surahs is the first that the evaluation carried out includes all the use of the force that in man begins to produce a work or deed. The two types of evaluation used are evaluations to test human abilities against various aspects of life problems experienced by humans.